Evaluation of commercial HPV assays in the context of post-treatment follow-up: Scottish Test of Cure Study (STOCS-H). Issue 6 (16th January 2014) - Cubie, H A; Canham, M; Moore, C; Pedraza, J; Graham, C; Cuschieri, K
Abstract : Aims: Human papillomavirus (HPV) testing is more sensitive than cytology for detection of residual/recurrent cervical disease after lesion treatment. Several HPV test comparison studies have been performed within triage and screening populations, but data on their comparative performance in a test of cure context is lacking. This study aims to address this gap. Methods: We compared the technical and clinical performance of Abbott RealTi m e High risk (HR)-HPV, Genprobe Aptima PV, Hologic Cervista HPV-HR, Qiagen Hybrid Capture 2 and Roche cobas HPV in the Early Implementation phase of a 'test of cure' service within the Scottish Cervical Screening Programme. Results: Valid results with all five HPV Tests from 1020 first samples taken ∼6 months post-treatment showed HPV positivity ranging from 17.84% to 26.96%. There was perfect agreement in 74%, and greatest variation between assays was observed in cytologically negative samples. Clinical performance was judged on cumulative incidence of cervical intraepithelial neoplasia 2+ (CIN2+) during follow-up (mean: 13.2 months). There were 23 cases of CIN2+ of which 14 were CIN3+. All assays, including cytology, were 100% sensitive for detection of CIN3+. Of the nine cases of residual CIN2, three assays detected all, one assay missed one and one assay missed two cases. Specificity ranged from 75% to 84% according to assay. Conclusions: All assays were sensitive for detection of CIN2+ at 6 months post-treatment. The range of positivity equated to a 50% increase between assays with the lowest and highest positivity rates. The relevance of HPV positivity in the absence of cytological abnormalities requires longer follow-up to determine whether additional tools for risk stratification are required.